Effects of foot and ankle mobilisations combined with home stretches in people with diabetic peripheral neuropathy: a proof-of-concept RCT - Lepesis, V.; Paton, J.; Rickard, A.; Latour, Jos; Marsden, J. (2023)
Introduction: People with diabetic peripheral neuropathy (DPN) and limited joint mobility syndrome (LJMS) can experience increased forefoot peak plantar pressures (PPPs), a known risk factor for ulceration. The aim of this study was to investigate whether ankle and 1st metatarsophalangeal (MTP) joint mobilisations and home-based stretches in people with DPN improve joint range of motion (ROM) and reduce forefoot PPPs. Design and methods: Sixty-one people with DPN (IWGDF risk 2), were randomly assigned to a 6-week programme of ankle and 1st MTP joint mobilisations (n = 31) and home-based stretches or standard care only (n = 30). At baseline (T0); 6-week post intervention (T1) and at 3 months follow-up (T2), a blinded assessor recorded dynamic ankle dorsiflexion range using 3D (Codamotion) motion analysis and the weight bearing lunge test, static 1st MTP joint dorsiflexion ROM, dynamic plantar pressure and balance. Results: At T1 and T2 there was no difference between both groups in ankle dorsiflexion in stance phase, plantar pressure and balance. Compared to the control group, the intervention group showed a statistically significant increase in static ankle dorsiflexion range (Left 1.52 cm and 2.9cms, Right 1.62 cm and 2.7 cm) at 6 (T1) and 18 weeks (T2) respectively p < 0.01). Between group differences were also seen in left hallux dorsiflexion (2.75°, p < 0.05) at T1 and in right hallux dorsiflexion ROM (4.9°, p < 0.01) at T2 follow up. Further, functional reach showed a significant increase in the intervention group (T1 = 3.13 cm p < 0.05 and T2 = 3.9 cm p < 0.01). Intervention adherence was high (80%). Conclusions: Combining ankle and 1st MTP joint mobilisations with home-based stretches in a 6-week programme in people with DPN is effective in increasing static measures of range. This intervention may be useful for improving ankle, hallux joint mobility and anteroposterior stability limits in people with diabetes and neuropathy but not for reducing PPP or foot ulcer risk. Trial registration: https://classic.clinicaltrials.gov/ct2/show/NCT03195855 .